Topological phase transitions in four dimensions - Defenu, Nicolò; Trombettoni, Andrea; Zappalà, Dario (Nuclear physics. B, Particle physics, 2021)
We show that four-dimensional systems may exhibit a topological phase transition analogous to the well-known Berezinskii-Kosterlitz-Thouless vortex unbinding transition in two-dimensional systems. We study a suitable generalization of the sine-Gordon model in four dimensions and the renormalization group flow equation of its couplings, showing that the critical value of the frequency is the square of the corresponding value in 2D. The value of the anomalous dimension at the critical point is determined (η=1/32) and a conjecture for the universal jump of the superfluid stiffness (4/π2) presented.
Available online 28 December 2020
Gesehen am 14.09.2022